Cancer-Related Anemia Is a Risk Factor for Medium-Term Postoperative Cognitive Dysfunction in Laparoscopic Surgery Patients: An Observational Prospective Study - Huimei Huang; Fei Lin; Liming Cen; Ren Jing; Linghui Pan (Neural Plasticity)
Anemia in the elderly may impair cognitive function. Our primary objective was to determine whether cancer-related anemia was associated with postoperative cognitive dysfunction (POCD) in nonelderly patients. We conducted an observational prospective study of 177 patients scheduled for laparoscopic surgery. Patients aged 18-64 were divided into two groups according to whether they were anemic due to cancer or not. The cognitive function was assessed by the Mini-Mental State Examination (MMSE) 1 day before and 1 week after operation. The cognitive function of the patients was evaluated by using the Telephone Interview for Cognitive Status-Modified (TICS-M) 3 months after operation. The quality of life of patients was evaluated after operation. The hemoglobin level and other clinical data were recorded before operation. Of the 170 patients, 100 without anemia and 70 anemia patients had been evaluated 1 week after operation. POCD was detected in 43 cases (25.3% of 170 cases) at 1 week and 30 cases (19% of 158 cases) at 3 months postoperatively. Anemia was an independent risk factor for 3-month POCD occurrence (P=0.034). The education level of the patients who had POCD at 1 week and 3 months after operation was lower (P<0.001, P=0.011, respectively). Age was independently associated with the incidence of POCD at 3 months (P=0.011). In general, these findings suggested that anemia may increase the incidence of medium-term POCD in cancer patients undergoing laparoscopic surgery.